2019
DOI: 10.3390/brainsci9010013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Behavioral Phenotypes of Fmr1 KO, Fxr2 Het, and Fmr1 KO/Fxr2 Het Mice

Abstract: Fragile X syndrome (FXS) is caused by silencing of the FMR1 gene leading to loss of the protein product fragile X mental retardation protein (FMRP). FXS is the most common monogenic cause of intellectual disability. There are two known mammalian paralogs of FMRP, FXR1P, and FXR2P. The functions of FXR1P and FXR2P and their possible roles in producing or modulating the phenotype observed in FXS are yet to be identified. Previous studies have revealed that mice lacking Fxr2 display similar behavioral abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…Conversely, both juvenile and adult Fmr1-Δ exon 8 rats showed an increased number of total entries in the arms of the elevated plus maze when compared to WT controls, thus confirming the hyperlocomotion displayed by Fmr1-Δ exon 8 rats across development. In line with these results, the extensively characterized Fmr1-KO mouse model of FXS has been shown to display motor alterations and hyperactivity [63][64][65][66][67] , although normal locomotor activity has also been also reported in rat models of FXS 68,69 . Conversely, we found that Fmr1-Δ exon 8 rats did not show stereotypic/repetitive behaviors in the hole-board test, as the number of head dippings did not differ from their WT controls.…”
Section: Discussionsupporting
confidence: 54%
“…Conversely, both juvenile and adult Fmr1-Δ exon 8 rats showed an increased number of total entries in the arms of the elevated plus maze when compared to WT controls, thus confirming the hyperlocomotion displayed by Fmr1-Δ exon 8 rats across development. In line with these results, the extensively characterized Fmr1-KO mouse model of FXS has been shown to display motor alterations and hyperactivity [63][64][65][66][67] , although normal locomotor activity has also been also reported in rat models of FXS 68,69 . Conversely, we found that Fmr1-Δ exon 8 rats did not show stereotypic/repetitive behaviors in the hole-board test, as the number of head dippings did not differ from their WT controls.…”
Section: Discussionsupporting
confidence: 54%
“…In particular, we observe a significant increase in marbles buried in the marble burying test and an increase in nesting behavior in the fragile X animals. Our marble burying data are consistent with the current understanding that increased burrowing behavior in this assay is indicative of increased anxiety-like behaviors in Fmr1 −/− mice [76][77][78]. Our nest-building data indicate that FXS animals engage in more nest-building behavior than wild type, contrary to previously reported data [79][80][81].…”
Section: Discussionsupporting
confidence: 89%
“…Beyond repeat expansions in the FMR1 gene, a number of rare pathogenic point mutations have been reported that cause developmental delay and ID reminiscent of FXS [153][154][155][156][157]. Further evidence suggests that mutations in the autosomal homolog FXR2 gene might also contribute to ID [158][159][160]. Whilst variants affecting the related FXR1 gene confer risk to schizophrenia, bipolar disorder, and autism [161][162][163][164][165], the genetic link between FMR1 and psychiatric disorders derives from enrichment of association within the gene targets of FMRP (among which the fragile-X family genes themselves are included).…”
Section: Fmrp and Fmrp Targets In Psychiatric Genomic Studiesmentioning
confidence: 99%